A new species of Calea (Neurolaeneae, Asteraceae) from the Espinhaço Range, Minas Gerais, Brazil - Reis E Silva, Genilson Alves Dos; Nakajima, Jimi Naoki (Phytotaxa, 2020)
A new species of Calea sect. Calea, endemic to the rocky grasslands of the municipality of Diamantina, Minas Gerais, southeastern Brazil, is described. Calea diamantinensis is morphologically similar to Calea lantanoides which differs by its leaf blade elliptic (vs. ovate to widely ovate), margin entire and straight (vs. crenate and revolute), surface solely glandular-punctuated (vs. villous), receptacle paleae obtrullate (vs. narrowly elliptic), capitulescence composed by 3–4 heads (vs. 6–12 heads), cypselae glandular-punctuated ca. 2.7–3 mm long (vs. non-glandular, ca. 1.8–2.5 mm long) and pappus scales ca. 15–17 (vs. 20–25). Illustration, photos, distribution map, habitat considerations and conservation status are provided, as well as an identification key for Calea species from the municipality of Diamantina, Minas Gerais.